(untitled) (Journal of Laboratory Animal Science, 2024)
Modern vivarium operation requires collective efforts by cross-functional teams especially within the collaborative research organizations for the successful outcomes of comprehensive laboratory animal care program. The drug discovery with rapid screening turnovers and innovative approaches demands infrastructure expansion by increasing several other capabilities in vivarium. The strategic portfolio changes and therapeutic areas closure retained several high-end equipment’s left unused that eventually occupied space in the barrier system which intricate daily operations and space management became challenging over the period. The vivarium facility was under continuous improvement by the quality assurance program based on monthly independent audit reports and compiled the compliance including animal welfare standards of at least 5 years period. Corporate initiatives such as Kaizen events, 5S concepts, Gemba walk and green labs certifications were implemented systematically at various phases across the organization including vivarium. The leadership team was a driving force behind the lean management practices and its implementation. The quality assurance program was able to bring out several improved operational processes notably by creating an additional quarantine space; repurposing high-end equipment for other investigators to support their ongoing programs; effective space utilization by creating in-house diagnostic laboratory; donating low-density animal racks for academic institutions as part of educational outreach efforts; containment of solid radioactive waste disposal by compaction process for longer half-life radioisotopes. In conclusion, lean management practices collectively demonstrated a measurable outcome in terms of continuous process improvement, effective vivarium management by ensuring compliance based on periodical observations without compromising animal welfare, conservation of energy and resources, effective space utilization and systematic implementation of 5S concepts by repurposing of equipment to other laboratories. Overall, the system-driven process has improved the standards with better performance that eventually enhanced the quality and productivity at the laboratory animal facility